Characterization of the DMD/BMD patient population in Czech Republic and Slovakia using an innovative registry approach - Brabec, Petr; Vondrácek, Petr; Klimes, Daniel; Baumeister, Sarah; Lochmüller, Hanns; Pavlík, Tomás; Gregor, Jakub (Neuromuscular disorders, 2009)
Effective planning of clinical trials requires an appropriate number of patients who fulfil given inclusion criteria. In the case of so called "orphan" diseases, such as Duchenne and Becker muscular dystrophy (DMD/BMD), the number of suitable patients within one country is usually limited. We developed a detailed registry of Czech and Slovak DMD/BMD patients which may contribute to cooperation on the European level. The registry uses internet and database technologies with a multilevel architecture. Patients may view their own data. As of May 2008, 163 patients have been registered in the database. The registry provides a detailed phenotypic and genotypic description of patients. The main purpose of such a registry is the time-effective recruitment of eligible patients for a clinical trial or therapy and may allow the anticipation of possible future effects of appropriate therapy on individual patients. The importance of the DMD/BMD patient registries has recently also been rising with new clinical trials focused on mutation-specific approaches. Other outputs include assessment of epidemiology, phenotype and genotype relationships, or standards of care.
Keywords: Muscular Dystrophy, Duchenne; Registries; sběr dat; Humans; Genetic Carrier Screening; výběr pacientů; dítě; registrace; mutační analýza DNA; Child; Patient Selection; Female; detekce genetických nosičů; mutace; Muscle Proteins; lidé; Data Collection; Databases as Topic; Slovakia; Slovenská republika; DNA Mutational Analysis; svalové proteiny; ženské pohlaví; Male; Genetic Predisposition to Disease; genetická predispozice k nemoci; klinické zkoušky jako téma; Czech Republic; databáze jako téma; genetické testování; Clinical Trials as Topic; Genetic Testing; Duchennova muskulární dystrofie; Česká republika; mužské pohlaví; Mutation